A Piloted Notch Time-Frequency Information Based Variable Step-Size Algorithm - Chobey, Dinesh Kumar (2016)
In this paper, we have proposed a new steering direction determination mechanism and step-size update algorithm for piloted adaptive notch filter architecture. A timedomain averaging based gradient analysis of the piloted notch cost function has been utilized to determine the direction of the main notch with respect to the input sinusoid frequency. The steering direction will indicate the distance between the frequency of the input sinusoid and the zero of the main notch. This frequency domain information has been interleaved with time domain information to develop a novel algorithm for determination of variable step-sizes for improved speed of convergence with comparatively huge reduction in steady-state mean square error (MSE). The simulation results verifies the excellent performance exhibited by our proposed steering mechanism and the step-size update algorithm over original piloted adaptive notch filter with respect to the speed of convergence and MSE.